2020
DOI: 10.1371/journal.ppat.1009103
|View full text |Cite
|
Sign up to set email alerts
|

The CH1α domain of mucosal gp41 IgA contributes to antibody specificity and antiviral functions in HIV-1 highly exposed Sero-Negative individuals

Abstract: The antibody molecule comprises a variable domain conferring antigen specificity and affinity distinct from the heavy chain constant (CH) domains dictating effector functions. We here interrogate this paradigm by evaluating the unique influence of the CH1α domain on epitope specificity and functions using two mucosal gp41-specific Fab-IgAs (FabA) derived from HIV-1 highly-exposed but persistently seronegative individuals (HESN). These HESN develop selectively affinity-matured HIV-1-specific mucosal IgA that ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Such high-risk subjects are referred to as HIV-exposed seronegative (HESN) individuals and include sex workers, HIV-status discordant couples, intravenous drug users, and children born to untreated HIV-infected mothers. Relative resistance to HIV infection is likely multi-factorial and several studies have identified innate immune and anti-inflammatory factors, HIV-specific T-and B-cell responses, increased regulatory T-and B-cell activity as well as genetic and epigenetic correlates to this phenotype [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Such high-risk subjects are referred to as HIV-exposed seronegative (HESN) individuals and include sex workers, HIV-status discordant couples, intravenous drug users, and children born to untreated HIV-infected mothers. Relative resistance to HIV infection is likely multi-factorial and several studies have identified innate immune and anti-inflammatory factors, HIV-specific T-and B-cell responses, increased regulatory T-and B-cell activity as well as genetic and epigenetic correlates to this phenotype [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The mucosal humoral responses in BAL contain secretory IgA and IgG, produced locally in the mucosa prior to secretion in the alveolar space, and have an antigenic repertoire distinct from the serum humoral response ( 14 , 26 , 60 ). We found that both SARS-CoV-2-specific IgA and IgG responses developed simultaneously after a week of infection when the virus replicates in BAL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nasal vaccination could not only be used for initial vaccination but also as a boost ( 85 , 86 ). Hence, anti-spike/N IgA could also eliminate virally infected cells by ADCC ( 87 ) or ADCP ( 77 ) as shown in other mucosal viral diseases ( 14 , 26 , 60 ) using innate immune cells expressing Fcα-receptor and acting as second-chance protection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of the Fab isotype, including that of the CH1 domain, also remains a parameter to be studied. In this respect, we revealed that the CH1 domain plays a crucial role in Fab antigen recognition (both in affinity and specificity) with a superiority of CH1α over CH1γ ( 127 ). Surprisingly, the higher molecular weight of Fcα-Fcγ or Fcγ-Fcγ tandem chimeras compared to parental Abs was not taken into account in these studies, probably introducing a bias.…”
Section: Chimeric Antibodies Containing Fcγ-fcα Enhance Fc-mediated F...mentioning
confidence: 97%